The promotion of self-regulation through parenting interventions. - Sanders, M.; Mazzucchelli, Trevor (Springer New York LLC, 2013)
The capacity for a parent to self-regulate their own performance is argued to be a fundamental process underpinning the maintenance of positive, nurturing, non-abusive parenting practices that promote good developmental and health outcomes in children. Deficits in self-regulatory capacity, which have their origins in early childhood, are common in many psychological disorders, and strengthening self-regulation skills is widely recognised as an important goal in many psychological therapies and is a fundamental goal in preventive interventions. Attainment of enhanced self-regulation skills enables individuals to gain a greater sense of personal control and mastery over their life. This paper illustrates how the self-regulatory principles can be applied to parenting and family-based interventions at the level of the child, parent, practitioner and organisation. The Triple P—Positive Parenting Program, which uses a self-regulatory model of intervention, is used as an example to illustrate the robustness and versatility of the self-regulation approach to all phases of the parent consultation process.